Historical analysis of development of strategic management system and its accounting provision - V.P. Hryn (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The necessity of analysis of the historical development of the strategic management system and its accounting support has been substantiated. The peculiarities of the emergence of the concept “strategy” and the procedure for its use in economic science has been analyzed. The stages (phases) of the strategic management formation process and the role of the accounting system in them (financial planning (budgeting), forecast strategic planning, external-oriented strategic planning, integrated strategic management) have been allocated. It has been established that the modern concept of strategic management was formed in the mid-1980s by merging strategic planning with companies’ management system. The role of the external environment of the activity of enterprises in the conditions of globalization of the world economy in the process of transformation of the system of strategic management has been determined. The expediency of using the requirements of the subjects of strategic control implementation to the accounting information as one of the directions of development of the accounting provision of strategic management has been grounded.